2012
DOI: 10.3390/nu4101382
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index (BMI) Trajectories from Birth to 11.5 Years: Relation to Early Life Food Intake

Abstract: Recent research has shown that the pattern of change over time, or trajectory, of body mass index (BMI) varies among children. However, the factors that underlie the heterogeneity in these trajectories remain largely unexplored. Our aim was to use a growth mixture model to empirically identify classes of BMI trajectories (from birth to 11.5 years) and examine the effects of breastfeeding, introduction of solids, as well as food and nutrient intake at 18 months on these BMI trajectories. We identified three BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(105 citation statements)
references
References 30 publications
6
97
0
2
Order By: Relevance
“…Developmental trajectories in children and adolescents were described in different settings but study comparisons are inappropriate due to differences in statistical solutions, growth modelling 20,21 versus growth mixture modelling (a group-based approach); 22-27 great heterogeneity in age ranges and differences in the outcome modelled, mostly using BMI [25][26][27] or BMI z-score. 20,[22][23][24] Adiposity differences between trajectories appeared in the first years of life and there was a low probability (about 10%) of changing trajectory from adolescence onwards (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Developmental trajectories in children and adolescents were described in different settings but study comparisons are inappropriate due to differences in statistical solutions, growth modelling 20,21 versus growth mixture modelling (a group-based approach); 22-27 great heterogeneity in age ranges and differences in the outcome modelled, mostly using BMI [25][26][27] or BMI z-score. 20,[22][23][24] Adiposity differences between trajectories appeared in the first years of life and there was a low probability (about 10%) of changing trajectory from adolescence onwards (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies indicate that BMI percentiles increase gradually over time in children. 42, 43 However, baseline BMI is a strong risk factor for eventual development of obesity, and children that become obese by age 3 to 5 years are likely to remain obese. 43-46 Therefore, the misclassification that is likely to result from our use of baseline BMI category as opposed to changes in BMI over time should be minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of four groups agrees with the results reported by Carter et al, 11 based on five z-BMI measurements between ages 4 and 10, and those of Mustillo et al, 13 drawn from annual weight and height measurements between ages 9 and 16 years. While other authors have reported three distinct trajectory groups, [8][9][10] these studies were limited by maternal reported heights and weights 10 or did not analyse standardised BMI. [8][9] Our results also demonstrate that the broad groupings of growth that we identified had clearly detectable effects on body size at age 9 years, with the group of children in the high growth group in early childhood showing a fourfold increase in odds of overweight or obesity at age 9 years.…”
Section: Effect Of Antenatal and Postnatal Exposures On Growth Trajecmentioning
confidence: 92%
“…While other authors have reported three distinct trajectory groups, [8][9][10] these studies were limited by maternal reported heights and weights 10 or did not analyse standardised BMI. [8][9] Our results also demonstrate that the broad groupings of growth that we identified had clearly detectable effects on body size at age 9 years, with the group of children in the high growth group in early childhood showing a fourfold increase in odds of overweight or obesity at age 9 years. Those children in the accelerated growth trajectory group in early childhood had a 15-fold increase in odds of overweight or obesity at age 9 years.…”
Section: Effect Of Antenatal and Postnatal Exposures On Growth Trajecmentioning
confidence: 92%
See 1 more Smart Citation